Phytochemical and Nutritional Properties of Sumac (Rhus Coriaria): A Potential Ingredient for Developing Functional Foods - Zannou, Oscar; Oussou, Kouame F.; Chabi, Ifagbemi B.; Alamou, Fadel; Awad, Nour M. H.; Miassi, Yann E.; Ibrahim, Salam A. (Keai Publishing Ltd, 2025)
Sumac (Rhus coriaria) is a flowering plant that is widely consumed for its promoting health benefits and used in food preparations as a spice in the Mediterranean region. It is a high shrub or small tree with imparipinnate leaves, villus and red fruits with one-seeded drupe, and small greenish-white flowers. The nutraceutical and pharmaceutical potential of sumac makes it a remarkable functional food. In this review, the phytochemical and nutritional properties of sumac as an under valorized functional food have been discussed. Flavonoids, anthocyanins, phenolic acids, and organic acids have been reported as dominant phytochemicals in sumac, which are well known for their pharmacological properties that attract many consumers to commonly choose sumac in their diet as well as food preparations. The remarkable volatile compounds present in sumac give it a unique aroma that increases its acceptance by consumers and potential use in the food industry. Sumac has been evaluated for a broad range of nutritional and pharmacological activities such as antioxidant, antinociceptive, anti-inflammatory, anti-diabetic, hepatoprotective, cardioprotective, anticancer, anti-infertility, and neuroprotective potential. This review has also briefly outlined the safety concerns concerning the use of sumac in terms of toxicology and interactions. (c) 2025 Beijing Academy of Food Sciences. Publishing services by Elsevier B.V. on behalf of KeAi Communications Co., Ltd. This is an open access article under the CCBY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/)
Chabi, Ifagbémi Bienvenue/0000-0002-9987-9080; Güçlü, Gamze/0000-0001-7317-6101; Pashazadeh, Hojjat/0000-0001-8932-8165;
Keywords: Sumac (Rhus Coriaria); Functional Food; Nutraceutical; Bioactive Compounds